2014
DOI: 10.1128/aem.01061-14
|View full text |Cite
|
Sign up to set email alerts
|

Revision of N2O-Producing Pathways in the Ammonia-Oxidizing Bacterium Nitrosomonas europaea ATCC 19718

Abstract: 2 ؊ reduction using hydrazine as an electron donor revealed that an alternate nitrite reductase to NirK is present and active. These experiments also clearly demonstrated that NorB was the sole nitric oxide reductase for nitrifier denitrification. The results of this study expand the enzymology for nitrogen metabolism and N 2 O production by N. europaea and will be useful to interpret pathways in other ammonia oxidizers that lack NirK and/or NorB genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 35 publications
4
98
2
Order By: Relevance
“…NirK generally functions to reduce NO 2 -to NO in denitrification or nitrifier denitrification pathways. NirK deletion variants of N. europaea show no disruption in N 2 O production under anaerobic conditions, which suggests that NirK is unnecessary for nitrifier denitrification in these organisms (37,38). However, these variant strains exhibit considerably decreased NO 2 -production.…”
Section: Hao Stoichiometrically Oxidizes Nh 2 Oh To No Under Anaerobicmentioning
confidence: 98%
“…NirK generally functions to reduce NO 2 -to NO in denitrification or nitrifier denitrification pathways. NirK deletion variants of N. europaea show no disruption in N 2 O production under anaerobic conditions, which suggests that NirK is unnecessary for nitrifier denitrification in these organisms (37,38). However, these variant strains exhibit considerably decreased NO 2 -production.…”
Section: Hao Stoichiometrically Oxidizes Nh 2 Oh To No Under Anaerobicmentioning
confidence: 98%
“…Is79 and N. europaea (20,66). During ammonia oxidation, NirK is hypothesized to act as an electron sink and prevent the buildup of the toxic intermediate hydroxylamine in AOB (67,68). NirK has been shown to be essential for efficient ammonia oxidation in N. europaea, with ammonia oxidation rates decreasing in nirK mutants compared to the rate in the wild type (68).…”
Section: Discussionmentioning
confidence: 99%
“…During ammonia oxidation, NirK is hypothesized to act as an electron sink and prevent the buildup of the toxic intermediate hydroxylamine in AOB (67,68). NirK has been shown to be essential for efficient ammonia oxidation in N. europaea, with ammonia oxidation rates decreasing in nirK mutants compared to the rate in the wild type (68). Since the NO 2 Ϫ concentration in the chemostats decreased from 4,653 M in the absence of N. winogradskyi to below 15 M when N. winogradskyi was present (see Table S3 in the supplemental material), our results suggest that NirK in Nitrosomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, gene expression data reported by Jiang et al represented transitional and not steadystate conditions (6). Other studies have suggested that N 2 O is produced via reduction of nitric oxide (NO) formed either by reduction of NO 2 Ϫ or by incomplete oxidation of NH 2 OH (15)(16)(17). N 2 O production by AOB has traditionally been associated with high NH 4 ϩ /NH 3 and NO 2 Ϫ concentrations and with low oxygen conditions (18)(19)(20), and further studies are needed to confirm the mechanism of N 2 O production under IC-limiting conditions.…”
mentioning
confidence: 99%